El segle XX: la modernització d’Andorra - Dot Jutglà, Esteve (Documents d’Anàlisi Geogràfica, 2008)
LLUELLES, Maria Jesús i altres El segle XX: la modernització d’Andorra Lleida; Andorra: CCIS; Pagès Editors, 2004; 559 p. ISBN: 84-9779-225-4